Perancangan Antarmuka Pengguna (UI/UX) Aplikasi Fun Run Menggunakan Metode Design Thinking - Iswanti, Siti; Muthi’ah Sari, Khofifah Indah; Oktaviani, Adelia (Journal of Information Systems and Business Technology, 2025)
Digital technology advancement has spurred sports applications promoting healthy lifestyles, with fun run events gaining popularity as community-based activities. However, participant registration and information management remain challenging due to inadequate digital integration. This research designs the FunRun application's UI/UX using Design Thinking's user-centered methodology through five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection involved interviews and observations with prospective participants and organizers to identify user needs and pain points. The outcome is an interactive Figma prototype featuring five core screens: home, registration, history, track and digital certificate. Usability testing via System Usability Scale (SUS) with 15 respondents achieved an average score of 87 ("Excellent" category), demonstrating Design Thinking's effectiveness in creating intuitive, efficient interfaces. FunRun improved registration efficiency by 50% and reduced data input errors by 73%. These findings validate user-centered design's impact on sports applications, serving as a reference for future digital solutions prioritizing user experience.